Maternal behavior influences development of a reflexive action pattern in the newborn rat. Issue 8 (8th June 2016) - Kauer, Sierra D.; Allmond, Jacob T.; Belnap, Starlie C.; Brumley, Michele R.
Abstract: This study examined the effect of maternal behavior on the expression and postnatal development of a reflexive behavior in rat pups. In neonatal rats, the leg extension response (LER) is a bilateral hyperextension of the hindlimbs in response to maternal anogenital licking (AGL). Past research has found that intranasal application of zinc sulfate (ZnSO4 ) to the dam induces hyponosmia, thereby reducing the incidence of AGL. In this study, pregnant dams received intranasal application of air (control), distilled water (control), or ZnSO4 on the day before birth and every other day thereafter until postnatal day 9 (P9). The LER was experimentally evoked in pups, using a vibrotactile device, at P1, P5, or P10. Pups born to ZnSO4 ‐treated dams showed significantly shorter bilateral LER durations and significantly smaller ankle angles than pups born to control dams. Reduction of overall maternal AGL approached significance, and afternoon AGL was significantly reduced. These data suggest that maternal behavior influenced development of the LER in rat pups, demonstrating the influence of maternal care on behavioral development during the perinatal period.